An E-Dictionary of Angklung Playing Based on Kodály Hand Signs in PKPBI Learning for Deaf Students - Dewa Ayu Kartika pratiwi; Anak Agung Gede Agung; I Gede Astawan (Universitas Pendidikan Ganesha, 2026)
Learning angklung playing skills in the PKPBI (Education and Development of the Indonesian Language) subject for deaf students still faces challenges, particularly the limited availability of media suitable for their visual and kinesthetic characteristics. Traditional learning tends to place the teacher as the primary resource, limiting students' independent practice and resulting in suboptimal sound detection and angklung playing skills. This study aims to analyze and develop an e-dictionary for angklung playing based on Kodaly hand signs and to test its feasibility, practicality, and effectiveness. This research is a developmental research using the ADDIE model. Subjects included experts and deaf students as users. Data were collected through questionnaires and tests using validation sheets, response questionnaires, and learning outcome tests. Data were then analyzed using descriptive quantitative and inferential methods. The results showed that the media had excellent feasibility, was practical to use, and was effective in improving sound detection and angklung playing skills in deaf students. The conclusion of this study is that the developed media is feasible, practical, and effective for use in PKPBI learning. Consequently, this media can be an innovative alternative to support more interactive, independent learning, and is tailored to the characteristics of deaf students.